Characterization of the crystalline quality of β-SiC formed by ion beam synthesis - S. Intarasiri (2018)
The ion beam synthesis (IBS) technique is applied to form crystalline silicon carbide (SiC) for future optoelectronics applications. Carbon ions at 80 and 40 keV were implanted into (1 0 0) high-purity p-type silicon wafers at room temperature and 400 °C, respectively, to doses in excess of 1017ions/cm2. Subsequent thermal annealing of the implanted samples was performed in a vacuum furnace at temperatures of 800, 900 and 1000 °C, respectively. Elastic recoil detection analysis was used to investigate depth distributions of the implanted ions and infrared transmittance (IR) measurement was used to characterize formation of SiC in the implanted Si substrate. Complementary to IR, Raman scattering measurements were also carried out. Levels of the residual damage distribution of the samples annealed at different temperatures were compared with that of the as-implanted one by Rutherford backscattering spectrometry (RBS) in the channeling mode. The results show that C-ion implantation at the elevated temperature, followed by high-temperature annealing, enhances the synthesis of crystalline SiC. © 2006 Elsevier B.V. All rights reserved.